Benefits of Deep Transcranial Magnetic Stimulation in Alzheimer Disease: Case Series. Issue 2 (June 2016) - Avirame, Keren; Stehberg, Jimmy; Todder, Doron
Abstract : Background: Patients diagnosed with Alzheimer disease (AD) show severe cognitive deficits. Decline in memory, language, and executive function have repeatedly been reported. Although AD affects 60% to 80% of demented elderly patients, there is currently no cure and limited treatment alternatives. Objectives: The aim of the study was to evaluate the feasibility of stimulating prefrontal cortex (PFC) with deep transcranial magnetic stimulation (dTMS) to ameliorate cognitive deficits in patients suffering from AD. Methods: Eleven patients (6 males; mean [SD] age, 76 [7] years) in moderate to severe stages of AD received dTMS over the PFC for 20 sessions. Computerized battery (Mindstreams [MS]) and neuropsychological testing (Addenbrooke Cognitive Examination [ACE]) were used to assess cognitive performance before and after treatment. Results: Compared with baseline, 60% of patients performed better on the MS battery and 77% of patients performed better on the ACE testing at the end of dTMS treatment. None of the patients performed worse on both tests at the end of treatment. The DTMS effects on the group mean in ACE and MS approached significance ( P = 0.065 and P = 0.086, respectively). A dTMS-induced improvement in the ACE was significant ( P = 0.001) on patients in more progressed stage (n = 6). Change in ACE negatively correlated with score at baseline. Conclusions: In sum, the current report of this novel technique indicates that deep stimulation might lead to preservation and even improvement of cognitive functions, at least during the time of treatment. Further examinations should report of long-term effects of this technique.